2020
DOI: 10.1007/s00405-020-06415-8
|View full text |Cite
|
Sign up to set email alerts
|

Modified submental platysmal adipomyofascial flap: is it a reliable alternate reconstructive option for small- to mid-sized defects especially in male patients with oral/oropharyngeal cancer?

Abstract: Purpose To introduce modified submental platysmal adipomyofascial flap as a new and viable hairless locoregional option for reconstruction of small-to mid-sized defects after ablative surgery in oral/oropharyngeal cancer patients keeping in mind the present pandemic situation. Methods An observational retrospective study was conducted using modified submental platysmal adipomyofascial flap as a locoregional reconstructive option for both intraoral and oropharyngeal defects in early-stage oral/oropharyngeal can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Oral cancer is clinically treated with surgical resection, supplemented with radiotherapy and chemotherapy [15], yet both have a high degree of recurrence and metastasis. Cisplatin is a clinical anticancer drug [16] with cell cycle nonspecificity. It inhibits the synthesis of DNA and RNA to exert anti-tumor effects.…”
Section: Discussionmentioning
confidence: 99%
“…Oral cancer is clinically treated with surgical resection, supplemented with radiotherapy and chemotherapy [15], yet both have a high degree of recurrence and metastasis. Cisplatin is a clinical anticancer drug [16] with cell cycle nonspecificity. It inhibits the synthesis of DNA and RNA to exert anti-tumor effects.…”
Section: Discussionmentioning
confidence: 99%
“…3 Moreover, Singh et al reported that the present scenario of the COVID-19 pandemic crisis requires alternative locoregional options for flap reconstruction in the head and neck rather than free flaps due to the increased emphasis on less operative time, shorter flap harvest time, and less postoperative complications and shorter hospital stay. 4 In our experience, four patients have undergone successful fistula repair with use of our novel stick-shaped platysma flap technique from June 2016 to April 2020 (Table 1). Herein, we report representative cases.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, Singh et al reported that the present scenario of the COVID‐19 pandemic crisis requires alternative locoregional options for flap reconstruction in the head and neck rather than free flaps due to the increased emphasis on less operative time, shorter flap harvest time, and less postoperative complications and shorter hospital stay 4 …”
Section: Introductionmentioning
confidence: 99%